Ceria particles and method for producing same

By firing a cerium compound with molybdenum compounds, ceria particles with controlled size and distribution are produced, addressing the limitations of existing methods and enhancing their catalytic and abrasive properties.

JP7601266B2Active Publication Date: 2024-12-17DIC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023575704
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-11
Publication Date
2024-12-17
Estimated Expiration
2041-06-11

AI Technical Summary

Technical Problem

Existing methods for producing ceria particles lack control over particle size and distribution, limiting their applications in catalyst carriers, abrasives, and solid electrolytes.

Method used

The production method involves firing a cerium compound in the presence of a molybdenum compound, such as molybdenum trioxide, lithium molybdate, or sodium molybdate, to create ceria particles with controlled particle size and distribution, where molybdenum is unevenly distributed on the surface layer, enhancing catalytic activity.

Benefits of technology

This method allows for the production of ceria particles with precise particle size and distribution, exhibiting improved catalytic activity and reduced agglomeration, suitable for uses in abrasives and solid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601266000002
    Figure 0007601266000002
  • Figure 0007601266000003
    Figure 0007601266000003
  • Figure 0007601266000004
    Figure 0007601266000004
Patent Text Reader

Abstract

The ceria particles contain molybdenum. In the ceria particles, the molybdenum may be unevenly distributed in a surface layer of the ceria particles. The ceria particles may have a crystallite diameter of a [100] plane of 250 nm or more. The ceria particles may have a crystallite diameter of a [101] plane of 300 nm or more. The median diameter D of the ceria particles calculated by a laser diffraction / scattering method may be 50 The diameter of the cerium compound may be 5.00 μm or more and 1000.00 μm or less. The method for producing ceria particles includes calcining a cerium compound in the presence of a molybdenum compound. The molybdenum compound may be at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate. In the method for producing ceria particles, the calcination temperature may be 800° C. or more and 1600° C. or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ceria particles and a method for producing the same. [Background technology]

[0002] It is known that cerium oxide (i.e., ceria) has a hardness that is optimal for polishing glass, silicon, etc., and that when a divalent or trivalent metal oxide is dissolved in it, the oxygen diffusion coefficient becomes extremely large. Because of these properties, ceria is expected to be used in catalyst supports and abrasives, as well as solid electrolytes used in fuel cells, oxygen pumps, oxygen sensors, etc., and it is necessary to control the particle size of ceria powder to suit these applications.

[0003] For example, Patent Document 1 discloses a method for producing nanoceria powder, which comprises mixing an organic solvent having a water content of 8 wt% or less and in which 0.01 to 1 mol / L of a cerium acid salt is dissolved, with an organic solvent having a water content of 8 wt% or less and in which 0.1 mol / L or more of an organic base agent is dissolved, producing a precipitate in which primary particles of at least one of cerium hydroxide or hydrated ceria are individually separated, separating this precipitate from the liquid phase, drying, and calcining the precipitate to produce nanoceria powder with no or almost no aggregation and an average particle size of 100 nm or less. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2002-201023 Summary of the Invention [Problem to be solved by the invention]

[0005] However, knowledge about conventional ceria particles and their manufacturing methods is limited, and there is still room for further study.

[0006] The present invention has been made in view of the above circumstances, and provides ceria particles having a controlled particle size and particle size distribution, and a method for producing the same. [Means for solving the problem]

[0007] That is, the present invention includes the following aspects. (1) Molybdenum-containing ceria particles. (2) The ceria particles according to (1) above, wherein the molybdenum is unevenly distributed in a surface layer of the ceria particles. (3) The ceria particles according to (1) or (2) above, wherein the crystallite size of the

[0100] plane of the ceria particles is 250 nm or more. (4) The ceria particles according to any one of (1) to (3), wherein the crystallite size of the

[0101] plane of the ceria particles is 300 nm or more. (5) The median diameter D of the ceria particles calculated by a laser diffraction / scattering method 50 The ceria particles according to any one of (1) to (4) above, having a particle size of 5.00 μm or more and 1000.00 μm or less. (6) a CeO2 content C1 relative to 100 mass% of the ceria particles determined by XRF analysis of the ceria particles is 60.00 mass% or more and 99.30 mass% or less; The ceria particles according to any one of (1) to (5), wherein the MoO3 content M1 relative to 100 mass% of the ceria particles, determined by XRF analysis of the ceria particles, is 0.05 mass% or more and 40.00 mass% or less. (7) a CeO2 content C2 relative to 100 mass% of the surface layer of the ceria particle, determined by XPS surface analysis of the ceria particle, is 10.00 mass% or more and 90.00 mass% or less; The ceria particles according to any one of (1) to (6), wherein the MoO3 content M2 relative to 100 mass% of the surface layer of the ceria particles, as determined by XPS surface analysis of the ceria particles, is 2.00 mass% or more and 70.00 mass% or less. (8) The ceria particles according to any one of (1) to (7), wherein a surface layer uneven distribution ratio M2 / M1 of a MoO3 content M2 relative to 100 mass% of the surface layer of the ceria particle, which is determined by XPS surface analysis of the ceria particle, to a MoO3 content M1 relative to 100 mass% of the ceria particle, which is determined by XRF analysis of the ceria particle, is 0.05 or more and 1400.00 or less. (9) A method for producing ceria particles according to any one of (1) to (8), comprising the steps of: A method for producing ceria particles comprising calcining a cerium compound in the presence of a molybdenum compound. (10) The method for producing ceria particles according to (9) above, wherein the molybdenum compound is at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate. (11) The method for producing ceria particles according to (9) or (10) above, wherein the firing temperature is 800° C. or higher and 1600° C. or lower. Effect of the Invention

[0008] According to the ceria particles and the method for producing the same of the above aspect, it is possible to obtain ceria particles having a controlled particle size and particle size distribution. [Brief description of the drawings]

[0009] [Figure 1] Figure 1 is a scanning electron microscope (SEM) image of the ceria particles of Example 1. The scale bar is 5.00 μm. [Diagram 2] Figure 2 is an SEM image of the ceria particles of Example 2. The scale bar is 5.00 μm. [Diagram 3] Figure 3 is an SEM image of the ceria particles of Comparative Example 1. The scale bar is 5.00 μm. [Figure 4] FIG. 4 is a graph showing the measurement results of the ceria particles of the examples and the comparative examples by the X-ray diffraction method (XRD method). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the ceria particles and the method for producing the ceria particles of the present invention will be described.

[0011] <Ceria particles> The ceria particles of the embodiment contain molybdenum. The ceria particles of the embodiment contain molybdenum, and have excellent properties such as catalytic activity derived from molybdenum.

[0012] In the ceria particle of the embodiment, the molybdenum is preferably unevenly distributed in a surface layer of the ceria particle. Here, in this specification, the term "surface layer" refers to a region within 10 nm from the surface of the ceria particle of the embodiment. This distance corresponds to the detection depth of the XPS used for measurement in the examples. Here, "distributed unevenly in the surface layer" refers to a state in which the mass of molybdenum or molybdenum compounds per unit volume in the surface layer is greater than the mass of molybdenum or molybdenum compounds per unit volume in areas other than the surface layer.

[0013] In the ceria particles of the embodiment, the fact that molybdenum is concentrated in the surface layer of the ceria particles can be confirmed by the fact that the MoO3 content (M2) relative to 100% by mass of the surface layer of the ceria particles, determined by XPS surface analysis of the ceria particles, is greater than the MoO3 content (M1) relative to 100% by mass of the ceria particles, determined by XRF (X-ray fluorescence) analysis of the ceria particles, as shown in the examples described later.

[0014] In the ceria particles of the embodiment, as an index that molybdenum is unevenly distributed in the surface layer of the ceria particles, the ceria particles of the embodiment preferably have a surface layer uneven distribution ratio (M2 / M1) of the MoO3 content (M2) to the MoO3 content (M1) of 0.05 or more and 1400.00 or less, more preferably 1.00 or more and 700.00 or less, even more preferably 20.00 or more and 500.00 or less, and particularly preferably 25.00 or more and 400.00 or less.

[0015] By distributing molybdenum or a molybdenum compound unevenly in the surface layer, excellent properties such as catalytic activity can be imparted more efficiently than when molybdenum or a molybdenum compound is present not only in the surface layer but also uniformly in the area other than the surface layer (inner layer).

[0016] The ceria particles of one embodiment produced by the production method of the embodiment can have a unique idiomorphic shape, such as a granular (spherical) or polyhedral shape, as shown in the examples described later.

[0017] In this specification, the term "polyhedral shape" means a shape having 6 or more faces, preferably 8 or more faces and 30 or less faces. The ceria particles according to the embodiment have a polyhedral shape formed by the flux method described below, and therefore form a single crystal structure.

[0018] In the production method of the ceria particles according to the embodiment, the particle size and molybdenum content of the obtained ceria particles can be controlled by controlling the amount and type of the molybdenum compound used in the production method described below.

[0019] The ceria particles of the embodiment preferably have a crystallite diameter of the

[0100] plane of 250 nm or more, more preferably 255 nm or more, even more preferably 260 nm or more, and particularly preferably 265 nm or more. The ceria particles of the embodiment may have a crystallite diameter of the

[0100] plane of 1000 nm or less, 500 nm or less, or 300 nm or less.

[0020] In this specification, the crystallite diameter of the <0100> plane of a ceria particle refers to the value of the crystallite diameter calculated by the Scherrer equation from the half-width of the peak assigned to the <0100> plane (i.e., the peak appearing near 2θ=28.5°) measured by X-ray diffraction (XRD).

[0021] The ceria particles of the embodiment preferably have a crystallite diameter of the

[0101] plane of 300 nm or more, more preferably 310 nm or more, even more preferably 330 nm or more, and particularly preferably 410 nm or more. The ceria particles of the embodiment may have a crystallite diameter of the

[0101] plane of 1000 nm or less, 700 nm or less, or 500 nm or less.

[0022] In this specification, the crystallite diameter of the

[0101] plane of a ceria particle refers to the value of the crystallite diameter calculated by the Scherrer equation from the half-width of the peak attributable to the

[0101] plane (i.e., the peak appearing near 2θ=47.5°) measured by X-ray diffraction (XRD).

[0023] An example of the ceria particles of the embodiment is a ceria particle having a crystallite diameter of 250 nm or more in the

[0100] plane and a crystallite diameter of 300 nm or more in the

[0101] plane. The ceria particles can have higher crystallinity.

[0024] The median diameter D of the ceria particles of the embodiment calculated by a laser diffraction / scattering method 50 is preferably 5.00 μm or more and 1000.00 μm or less, more preferably 6.00 μm or more and 100.00 μm or less, even more preferably 8.00 μm or more and 50.00 μm or less, and particularly preferably 12.00 μm or more and 30.00 μm or less.

[0025] The median diameter D of ceria particles calculated by the laser diffraction / scattering method 50 can be calculated as the particle size at which the volume cumulative percentage is 50% in the particle size distribution measured in a dry state using a laser diffraction particle size distribution analyzer.

[0026] The particle diameter D of the ceria particles of the embodiment calculated by a laser diffraction / scattering method 10is preferably 1.60 μm or more and 100.00 μm or less, more preferably 1.80 μm or more and 50.00 μm or less, and even more preferably 2.00 μm or more and 10.00 μm or less.

[0027] The particle size D of ceria particles calculated by the laser diffraction / scattering method 10 can be calculated as the particle size at which the volume cumulative percentage of small particles is 10% in the particle size distribution measured in a dry state using a laser diffraction particle size distribution analyzer.

[0028] The particle diameter D of the ceria particles of the embodiment calculated by a laser diffraction / scattering method 90 is preferably 9.00 μm or more and 1500.00 μm or less, more preferably 10.00 μm or more and 300.00 μm or less, and even more preferably 15.00 μm or more and 50.00 μm or less.

[0029] The particle size D of ceria particles calculated by the laser diffraction / scattering method 90 can be calculated as the particle size at which the volume cumulative percentage of small particles is 90% in the particle size distribution measured in a dry state using a laser diffraction particle size distribution analyzer.

[0030] The ceria particles of the embodiment contain ceria (cerium oxide). Examples of the cerium oxide that may be contained in the ceria particles of the embodiment include CeO2.

[0031] The ceria content in the ceria particles can be measured by XRF analysis. In the embodiment, the ceria particles have a CeO2 content C1 relative to 100 mass% of the ceria particles, which is determined by XRF analysis of the ceria particles, of preferably 60.00 mass% or more and 99.30 mass% or less, more preferably 90.00 mass% or more and 99.10 mass% or less, and even more preferably 93.00 mass% or more and 99.00 mass% or less.

[0032] The ceria particles of the embodiment contain molybdenum. The ceria particles of the embodiment have a MoO3 content M1 relative to 100 mass% of the ceria particles, which is determined by XRF analysis of the ceria particles, of preferably 0.05 mass% to 40.00 mass%, more preferably 0.05 mass% to 20.00 mass%, further preferably 0.05 mass% to 10.00 mass%, and particularly preferably 0.05 mass% to 2.50 mass%.

[0033] In the ceria particles of the embodiment, the upper and lower limit values ​​of the CeO2 content C1 and the MoO3 content M1 exemplified above can be freely combined. In addition, the values ​​of the CeO2 content C1 and the MoO3 content M1 can also be freely combined.

[0034] An example of the ceria particles of the embodiment is ceria particles having a CeO2 content C1 of 60.00 mass % or more and 99.30 mass % or less and a MoO3 content M1 of 0.05 mass % or more and 40.00 mass % or less.

[0035] The CeO2 content C1 and the MoO3 content M1 can be measured, for example, by XRF analysis using an X-ray fluorescence analyzer (Primus IV) manufactured by Rigaku Corporation.

[0036] The ceria content in the surface layer of the ceria particle can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. In the embodiment, the ceria particle has a CeO2 content C2 of 100 mass% of the surface layer of the ceria particle, which is determined by XPS surface analysis of the ceria particle, of preferably 10.00 mass% to 90.00 mass%, more preferably 10.00 mass% to 80.00 mass%, and even more preferably 10.00 mass% to 70.00 mass%.

[0037] In the embodiment, the ceria particles have a MoO3 content M2 relative to 100 mass% of the surface layer of the ceria particles, as determined by XPS surface analysis of the ceria particles, of preferably 2.00 mass% or more and 70.00 mass% or less, more preferably 10.00 mass% or more and 65.00 mass% or less, and even more preferably 20.00 mass% or more and 60.00 mass% or less.

[0038] In the ceria particles of the embodiment, the upper and lower limit values ​​of the CeO2 content C2 and the MoO3 content M2 exemplified above can be freely combined. In addition, the values ​​of the CeO2 content C2 and the MoO3 content M2 can also be freely combined.

[0039] An example of the ceria particles of the embodiment is ceria particles having a CeO2 content C2 of 10.00 mass % or more and 90.00 mass % or less and a MoO3 content M2 of 2.00 mass % or more and 70.00 mass % or less.

[0040] The above CeO2 content C2 refers to a value calculated as the CeO2 content relative to 100 mass% of the surface layer of the ceria particle by performing XPS surface analysis of the ceria particle using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element and converting the cerium content into an oxide.

[0041] The MoO3 content M2 is a value calculated by performing XPS surface analysis of the ceria particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, converting the molybdenum content into an oxide, and calculating the MoO3 content relative to 100% by mass of the surface layer of the ceria particles.

[0042] In addition to molybdenum, the ceria particles of the embodiment may further contain lithium, potassium, or sodium.

[0043] <Method of manufacturing ceria particles> The method for producing ceria particles according to the embodiment (hereinafter simply referred to as the "production method according to the embodiment") includes a step of calcining a cerium compound in the presence of a molybdenum compound. More specifically, the production method according to the embodiment may be a method for producing ceria particles, which includes mixing a cerium compound and a molybdenum compound to form a mixture, and calcining the mixture.

[0044] According to the method for producing ceria particles of the embodiment, it is possible to produce the ceria particles of the embodiment described above.

[0045] A preferred method for producing ceria particles includes a step of mixing a cerium compound and a molybdenum compound to form a mixture (mixing step), and a step of firing the mixture (firing step).

[0046] [Mixing process] The mixing step is a step of mixing a cerium compound and a molybdenum compound to obtain a mixture. The contents of the mixture will be described below.

[0047] (Cerium Compounds) The cerium compound is not limited as long as it can be turned into cerium oxide by firing. Examples of the cerium compound include cerium oxide, cerium hydroxide, and cerium oxalate, and cerium oxide is preferred. The cerium oxide may be Ce2O3 (cerium oxide (III)), CeO2 (cerium oxide (IV)), or cerium oxide composed of Ce2O3 and CeO2.

[0048] The shape of the calcined ceria particles does not substantially reflect the shape of the raw cerium compound. Therefore, any cerium compound may be suitably used, for example, in the form of a sphere, an amorphous structure, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc.

[0049] (Molybdenum Compounds) The molybdenum compound includes molybdenum oxide, molybdate compounds, and the like.

[0050] The molybdenum oxide includes molybdenum dioxide, molybdenum trioxide, etc., and is preferably molybdenum trioxide.

[0051] The molybdate compound is MoO4 2- , Mo2O7 2- , Mo3O 10 2- , Mo4O 13 2- , Mo5O 16 2- , Mo6O 19 2- , Mo7O 24 6- , Mo8O 26 4- The molybdenum oxoanion may be, but is not limited to, a salt compound of the molybdenum oxoanion such as those mentioned above. The molybdenum oxoanion may be an alkali metal salt, an alkaline earth metal salt, or an ammonium salt.

[0052] The molybdate compound is preferably an alkali metal salt of a molybdenum oxoanion, more preferably lithium molybdate, potassium molybdate or sodium molybdate, and even more preferably potassium molybdate or sodium molybdate.

[0053] In the manufacturing method according to the embodiment, the molybdate compound may be a hydrate.

[0054] The molybdenum compound is preferably at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate, and more preferably at least one compound selected from the group consisting of molybdenum trioxide, potassium molybdate, and sodium molybdate.

[0055] The manufacturing method according to the embodiment may include a step of calcining a cerium compound in the presence of a molybdenum compound and a potassium compound.

[0056] The manufacturing method of the embodiment may include a step (mixing step) of mixing a cerium compound, a molybdenum compound, and a potassium compound to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0057] Alternatively, the manufacturing method of the embodiment may include a step (mixing step) of mixing a cerium compound and a compound containing molybdenum and potassium to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0058] A compound containing molybdenum and potassium suitable as a fluxing agent can be produced, for example, in the firing process using a molybdenum compound and a potassium compound, which are cheaper and more readily available, as raw materials. Here, the use of a molybdenum compound and a potassium compound as fluxing agents and the use of a compound containing molybdenum and potassium as fluxing agents are both considered to be the use of a molybdenum compound and a potassium compound as fluxing agents, i.e., in the presence of a molybdenum compound and a potassium compound.

[0059] The manufacturing method according to the embodiment may include a step of calcining a cerium compound in the presence of a molybdenum compound and a sodium compound.

[0060] The manufacturing method of the embodiment may include a step (mixing step) of mixing a cerium compound, a molybdenum compound, and a sodium compound to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0061] Alternatively, the manufacturing method of the embodiment may include a step (mixing step) of mixing a cerium compound and a compound containing molybdenum and sodium to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0062] A compound containing molybdenum and sodium suitable as a fluxing agent can be produced, for example, in the firing process using a molybdenum compound and a sodium compound, which are cheaper and more readily available, as raw materials. Here, the use of a molybdenum compound and a sodium compound as fluxing agents and the use of a compound containing molybdenum and sodium as fluxing agents are both considered to be the use of a molybdenum compound and a sodium compound as fluxing agents, i.e., in the presence of a molybdenum compound and a sodium compound.

[0063] By calcining a cerium compound in the presence of a molybdenum compound and a potassium compound, or in the presence of a molybdenum compound and a sodium compound, it is possible to easily obtain ceria particles with a high molybdenum content, and it is also easy to adjust the particle size of the produced ceria particles. The reason for this is not clear, but the following reasons are considered. For example, K2MoO4 and Na2MoO4 are stable compounds and are difficult to volatilize during the calcination process, so they are unlikely to undergo rapid reactions during the volatilization process, making it easy to control the growth of ceria particles. In addition, it is considered that molten K2MoO4 and Na2MoO4 function like a solvent, and the particle size can be increased, for example, by extending the reaction time.

[0064] In the manufacturing method of the embodiment, the molybdenum compound is used as a fluxing agent. In the present specification, the manufacturing method using the molybdenum compound as a fluxing agent may be simply referred to as the "flux method". It is considered that the molybdenum compound reacts with the cerium compound at high temperature by the firing to form cerium molybdate, and then the cerium molybdate is further decomposed into cerium and molybdenum oxide at a higher temperature, and the molybdenum compound is taken into the ceria particles. The molybdenum oxide is sublimated and removed from the system, and during this process, the molybdenum compound reacts with the cerium compound to form the molybdenum compound on the surface layer of the ceria particles. More specifically, the mechanism of the formation of the molybdenum compound contained in the ceria particles is that the formation of Mo-O-Ce occurs on the surface layer of the ceria particles due to the reaction of molybdenum and Ce atoms, and the high-temperature firing causes Mo to be released, and the formation of molybdenum oxide or a compound having a Mo-O-Ce bond on the surface layer of the ceria particles is considered.

[0065] Molybdenum oxide that is not incorporated into the ceria particles can be recovered and reused by sublimation, which reduces the amount of molybdenum oxide that adheres to the surface of the ceria particles and maximizes the inherent properties of the ceria particles.

[0066] On the other hand, the alkali metal salt of the molybdenum oxoanion does not vaporize even at the calcination temperature range and can be easily recovered by washing after calcination. This reduces the amount of molybdenum compounds released outside the calcination furnace, and also allows for a significant reduction in production costs.

[0067] In the above flux method, for example, when a molybdenum compound and a potassium compound are used in combination, it is believed that the molybdenum compound and the potassium compound react to form potassium molybdate. At the same time, it is believed that the molybdenum compound reacts with a cerium compound to form cerium molybdate. Then, for example, in the presence of liquid potassium molybdate, cerium molybdate decomposes and grows into a crystal, thereby easily obtaining ceria particles with a large particle size and a high molybdenum content while suppressing the evaporation of the above flux (sublimation of MoO3).

[0068] (metal compound) A metal compound may be used during calcination if desired. The manufacturing method of the embodiment may include a step (mixing step) of mixing a cerium compound, a molybdenum compound, a potassium compound, and a metal compound to form a mixture prior to the calcination step, and may include a step (calcination step) of calcining the mixture.

[0069] The metal compound is not particularly limited, but preferably contains at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.

[0070] Examples of the Group II metal compound include magnesium compounds, calcium compounds, strontium compounds, and barium compounds.

[0071] Examples of the Group III metal compound include a scandium compound, an yttrium compound, and a lanthanum compound.

[0072] The above-mentioned metal compounds refer to oxides, hydroxides, carbonates, and chlorides of metal elements. For example, yttrium compounds include yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate. Of these, the metal compounds are preferably oxides of metal elements. These metal compounds include isomers.

[0073] Among these, the metal compounds of the third periodic elements, the metal compounds of the fourth periodic elements, the metal compounds of the fifth periodic elements, and the metal compounds of the sixth periodic elements are preferred, the metal compounds of the fourth periodic elements and the metal compounds of the fifth periodic elements are more preferred, and the metal compounds of the fifth periodic elements are even more preferred. Specifically, it is preferred to use magnesium compounds, calcium compounds, yttrium compounds, and lanthanum compounds, it is more preferred to use magnesium compounds, calcium compounds, and yttrium compounds, and it is particularly preferred to use yttrium compounds.

[0074] The metal compound is preferably used in a ratio of, for example, 0 mass % or more and 1.2 mass % or less (for example, 0 mol % or more and 1 mol % or less) relative to the total amount (total mass or total molar amount) of the cerium compound used in the mixing step.

[0075] In the manufacturing method of the embodiment, the blending amounts of the cerium compound and the molybdenum compound are not particularly limited, but preferably, 35% by mass or more of the cerium compound and 65% by mass or less of the molybdenum compound are mixed with respect to 100% by mass of the mixture, and the mixture is fired. More preferably, 40% by mass or more and 90% by mass or less of the cerium compound and 0.5% by mass or more and 60% by mass or less of the molybdenum compound are mixed with respect to 100% by mass of the mixture, and the mixture is fired. Even more preferably, 42% by mass or more and 50% by mass or less of the cerium compound and 38% by mass or more and 50% by mass or less of the molybdenum compound are mixed with respect to 100% by mass of the mixture, and the mixture is fired.

[0076] In the manufacturing method of the embodiment, the molar ratio of molybdenum atoms in the molybdenum compound to cerium atoms in the cerium compound (molybdenum / cerium) is preferably 0.01 or more, more preferably 0.10 or more, even more preferably 0.30 or more, and particularly preferably 0.50 or more. The upper limit of the molar ratio of molybdenum atoms in the molybdenum compound and cerium atoms in the cerium compound may be determined as appropriate. From the viewpoint of reducing the amount of molybdenum compound used and improving production efficiency, for example, the molar ratio (molybdenum / cerium) may be 5.00 or less, 4.00 or less, 3.00 or less, or 1.50 or less. An example of the numerical range of the molar ratio (molybdenum / cerium) is, for example, the molybdenum / cerium value may be 0.01 or more and 5.00 or less, 0.10 or more and 4.00 or less, 0.30 or more and 3.00 or less, or 0.50 or more and 1.50 or less.

[0077] It should be noted that the more the amount of molybdenum used relative to cerium, the larger the particle size of the ceria particles obtained, as indicated by the above particle size distribution.

[0078] By using various compounds within the above ranges, the amount of molybdenum compound contained in the obtained ceria particles becomes more appropriate, and ceria particles with a controlled particle size can be easily obtained.

[0079] [Firing process] The firing step is a step of firing the mixture. The ceria particles according to the embodiment are obtained by firing the mixture. As described above, this manufacturing method is called a flux method.

[0080] The flux method is classified as a solution method. More specifically, the flux method is a crystal growth method that utilizes the fact that the crystal-flux two-component phase diagram shows a eutectic type. The mechanism of the flux method is presumed to be as follows. That is, when a mixture of a solute and flux is heated, the solute and flux become liquid phase. At this time, since the flux is a flux, in other words, since the solute-flux two-component phase diagram shows a eutectic type, the solute melts at a temperature lower than its melting point and forms a liquid phase. If the flux is evaporated in this state, the concentration of the flux decreases, in other words, the effect of the flux in lowering the melting point of the solute is reduced, and the evaporation of the flux becomes the driving force to cause crystal growth of the solute (flux evaporation method). Note that the solute and flux can also cause crystal growth of the solute by cooling the liquid phase (slow cooling method).

[0081] The flux method has the advantages of being able to grow crystals at temperatures much lower than the melting point, being able to precisely control the crystal structure, and being able to form euhedral polyhedral crystals.

[0082] In the production of ceria particles by the flux method using a molybdenum compound as a flux, the mechanism is not necessarily clear, but it is presumed to be due to the following mechanism, for example. That is, when a cerium compound is fired in the presence of a molybdenum compound, cerium molybdate is first formed. At this time, as can be understood from the above explanation, the cerium molybdate grows ceria crystals at a temperature lower than the melting point of ceria. Then, for example, by evaporating the flux, the cerium molybdate decomposes, and the crystals grow, thereby obtaining ceria particles. That is, the molybdenum compound functions as a flux, and ceria particles are produced via an intermediate called cerium molybdate.

[0083] By the above-mentioned flux method, it is possible to produce ceria particles containing molybdenum, the molybdenum being unevenly distributed in the surface layer of the ceria particles.

[0084] The firing method is not particularly limited, and may be performed by a known, commonly used method. When the firing temperature exceeds 800°C, it is believed that the cerium compound and the molybdenum compound react to form cerium molybdate. Furthermore, when the firing temperature is 950°C or higher, it is believed that the cerium molybdate decomposes to form ceria particles. In addition, in the ceria particles, it is believed that the molybdenum compound is incorporated into the ceria particles when the cerium molybdate decomposes to form ceria and molybdenum oxide.

[0085] In addition, the state of the cerium compound and the molybdenum compound during firing is not particularly limited, and it is sufficient that the molybdenum compound is present in the same space so that the molybdenum compound can act on the cerium compound. Specifically, the molybdenum compound and the cerium compound may be simply mixed together in powder form with each other, mechanically mixed using a grinder or the like, or mixed using a mortar or the like, and may be mixed in a dry or wet state.

[0086] The firing temperature condition is not particularly limited, and is appropriately determined in consideration of the target particle size of the ceria particles, the formation of the molybdenum compound in the ceria particles, the shape of the ceria particles, etc. The firing temperature may be 900° C. or higher, which is close to the decomposition temperature of cerium molybdate, 950° C. or higher, or 1000° C. or higher.

[0087] The higher the calcination temperature, the more easily the particle shape is controlled and the larger the particle size of the ceria particles is obtained. From the viewpoint of efficiently producing such ceria particles, the calcination temperature is preferably 950° C. or higher, more preferably 1000° C. or higher, even more preferably 1100° C. or higher, and particularly preferably 1200° C. or higher.

[0088] Generally, to control the shape of ceria particles obtained after firing, it is necessary to perform high-temperature firing at over 2400°C, which is close to the melting point of ceria. However, there are significant challenges to be overcome in terms of the burden on the firing furnace and fuel costs in order to utilize this method industrially.

[0089] According to one embodiment of the present invention, even under conditions where the maximum sintering temperature for sintering a cerium compound is 1600° C. or lower, ceria particles can be formed efficiently at low cost.

[0090] Furthermore, according to the manufacturing method of the embodiment, idiomorphous ceria particles can be formed regardless of the shape of the precursor even at a firing temperature of 1600° C. or less, which is much lower than the melting point of ceria. From this viewpoint, the firing temperature is preferably 1500° C. or less, more preferably 1400° C. or less, and even more preferably 1300° C. or less.

[0091] The numerical range of the firing temperature for firing the cerium compound in the firing step may be, for example, 900°C or higher and 1600°C or lower, 900°C or higher and 1500°C or lower, 950°C or higher and 1400°C or lower, 1000°C or higher and 1300°C or lower, or 1100°C or higher and 1300°C or lower.

[0092] From the viewpoint of manufacturing efficiency, the heating rate may be 20°C / hour or more and 600°C / hour or less, 40°C / hour or more and 500°C / hour or less, or 80°C / hour or more and 400°C / hour or less.

[0093] Regarding the calcination time, it is preferable to raise the temperature to a predetermined calcination temperature in a range of 15 minutes to 10 hours and to hold the calcination temperature for a period of 5 minutes to 30 hours. In order to efficiently form ceria particles, it is more preferable to hold the calcination temperature for a period of 2 hours to 24 hours.

[0094] As an example, by selecting conditions of a firing temperature of 900° C. or more and 1600° C. or less and a firing temperature holding time of 2 hours or more and 24 hours or less, the ceria particles of the embodiment containing molybdenum can be easily obtained.

[0095] The firing atmosphere is not particularly limited as long as the effects of the manufacturing method of the embodiment can be obtained. For example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen, argon, or carbon dioxide is preferable, and an air atmosphere is more preferable when cost is taken into consideration.

[0096] The calcination apparatus is not necessarily limited, and a so-called calcination furnace can be used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and it is preferable to use a highly airtight calcination furnace so as to efficiently utilize the molybdenum oxide.

[0097] [Molybdenum removal process] The manufacturing method according to the embodiment may further include, after the firing step, a molybdenum removal step of removing at least a portion of the molybdenum, as necessary.

[0098] As described above, since molybdenum sublimes during firing, the molybdenum content present in the surface layer of the ceria particles can be controlled by controlling the firing time, firing temperature, etc., and the molybdenum content and state present in the layers other than the surface layer (inner layer) of the ceria particles can also be controlled.

[0099] Molybdenum may adhere to the surface of the ceria particles, and as a means other than the sublimation, the molybdenum may be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or the like.

[0100] In this case, the molybdenum content in the ceria particles can be controlled by appropriately changing the concentrations and amounts of water, the aqueous ammonia solution, and the aqueous sodium hydroxide solution used, as well as the washing locations and washing times.

[0101] [Crushing process] In the calcined product obtained through the calcination step, the ceria particles may aggregate and may not satisfy the suitable particle size range for the intended application, so that the ceria particles may be pulverized as necessary to satisfy the suitable particle size range.

[0102] The method for pulverizing the fired product is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.

[0103] [Classification process] The sintered product containing ceria particles obtained by the sintering step may be appropriately classified to adjust the particle size range. "Classification" refers to an operation of classifying particles into groups according to their size.

[0104] The classification may be either wet or dry, but from the viewpoint of productivity, dry classification is preferred. Dry classification includes classification by sieving, as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag, but from the viewpoint of classification accuracy, wind classification is preferred, and can be performed using a classifier such as an air classifier utilizing the Coanda effect, a swirling air classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier.

[0105] The above-mentioned pulverization step and classification step can be carried out at any stage required. Depending on whether or not pulverization or classification is performed and the selection of the conditions therefor, for example, the average particle size of the obtained ceria particles can be adjusted.

[0106] The ceria particles of the embodiment or the ceria particles obtained by the manufacturing method of the embodiment are preferably those which are less aggregated or are not aggregated, from the viewpoints that they easily exhibit their inherent properties, have excellent handling properties, and have excellent dispersibility when dispersed in a dispersion medium for use.

[0107] According to the manufacturing method of the above embodiment, ceria particles with little or no agglomeration can be easily manufactured, and therefore, there is an excellent advantage that ceria particles having the desired excellent properties can be manufactured with high productivity without performing the above-mentioned crushing step or classification step.

[0108] The ceria particles of the embodiment or the ceria particles obtained by the manufacturing method of the embodiment have the above-mentioned properties, and therefore are preferably used for, for example, an abrasive, a three-way catalyst, a solid electrolyte, and the like. EXAMPLES

[0109] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0110] <Production of ceria particles> [Comparative Example 1] 3.0 g of cerium oxide (manufactured by Aladdin) was placed in a crucible and fired in a ceramic electric furnace at 1100° C. for 24 hours. After cooling, the crucible was removed to obtain 3.0 g of a gray powder.

[0111] [Comparative Example 2] Cerium oxide (Aladdin) was used as is as a sample for Comparative Example 2.

[0112] [Example 1] 3.0 g of cerium oxide (manufactured by Aladdin), 2.71 g of molybdenum trioxide (manufactured by Chengdu Hongbo Industrial), 1.3 g of potassium carbonate, and 0.015 g of yttrium oxide were mixed in a mortar to obtain a mixture. The mixture obtained was placed in a crucible and fired in a ceramic electric furnace at 1300°C for 24 hours. After cooling, the crucible was removed to obtain 5.2 g of pale yellow powder. Next, 4.1 g of the obtained pale yellow powder was suspended in 30 g of ion-exchanged water and stirred for 2 hours, and then filtered and washed to obtain 2.9 g of pale yellow powder.

[0113] [Example 2] 3.0 g of cerium oxide (manufactured by Aladdin) and 3.0 g of sodium molybdate dihydrate (manufactured by Chengdu Hongbo Industrial) were mixed in a mortar to obtain a mixture. The mixture obtained was placed in a crucible and fired in a ceramic electric furnace at 1300°C for 24 hours. After cooling, the crucible was removed to obtain 4.6 g of pale pink powder. Next, 4.6 g of the obtained pale pink powder was suspended in 30 g of ion-exchanged water and stirred for 2 hours, and then filtered and washed to obtain 2.8 g of pale pink powder.

[0114] <Evaluation> The powders obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were used as sample powders and were evaluated as follows.

[0115] [Crystallite size measurement] Using an X-ray diffractometer (Rigaku Corporation, SmartLab) equipped with a high intensity, high resolution crystal analyzer (CALSA) as a detector, powder X-ray diffraction (2θ / θ method) measurements were performed under the following measurement conditions. Analysis was performed using the CALSA function of analysis software (PDXL) manufactured by Rigaku Corporation, and [ 100 The crystallite diameter of the ] plane was calculated using the Scherrer equation from the half-width of the peak appearing around 2θ = 28.5°, and 101 The crystallite diameter of the ] plane was calculated using the Scherrer equation from the half-width of the peak appearing near 2θ=47.5°. The results are shown in Table 1.

[0116] (Measurement conditions for powder X-ray diffraction method) Tube voltage: 45kV Tube current: 200mA Scan speed: 0.05° / min Scan range: 10° to 70° Step: 0.002° βs:20rpm Device standard width: 0.026° calculated using standard silicon powder (NIST, 640d) produced by the National Institute of Standards and Technology was used.

[0117] [Crystal structure analysis: XRD (X-ray diffraction) method] The sample powder was filled into a measurement sample holder with a depth of 0.5 mm, which was then set into a wide-angle X-ray diffraction (XRD) device (Ultima IV, Rigaku Corporation). Measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, scan speed of 2° / min, and a scan range of 10° to 70°.

[0118] [Particle size distribution measurement] The particle size distribution of the sample powder was measured in a dry state using a laser diffraction type dry particle size distribution analyzer (HELOS (H3355) & RODOS, manufactured by Japan Laser Co., Ltd.) under the conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar. The particle size at the point where the distribution curve of the volume cumulative percentage intersects with the horizontal axis at 10% from the small particle side was defined as D. 10 The particle diameter at the point where it intersects with the horizontal axis at 50% is D 50 The particle diameter at the point where the horizontal axis intersects with the 90% particle diameter from the small particle side is D 90 As such, we calculated the following:

[0119] [XRF (X-ray fluorescence) analysis] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), approximately 70 mg of sample powder was placed on filter paper, covered with PP film, and XRF (X-ray fluorescence) analysis was performed under the following conditions.

[0120] (Measurement conditions) EZ Scan Mode Measuring elements: F~U Measurement time: Standard Measurement diameter: 10mm Balance: None

[0121] The results of the CeO2 content (C1) relative to 100 mass% of the ceria particles and the MoO3 content (M1) relative to 100 mass% of the ceria particles were obtained by XRF analysis.

[0122] [XPS surface analysis] Surface elemental analysis of the sample powder was performed using an ULVAC-PHI QUANTERA SXM, with monochromated Al-Kα as the X-ray source, and X-ray photoelectron spectroscopy (XPS: X-ray photoelectron spectroscopy). The area was measured in a 1000 μm square area, and the average value of n=3 measurements was obtained in atom% for each element.

[0123] The cerium content and molybdenum content in the surface layer of the ceria particle obtained by XPS analysis were converted into oxides to determine the CeO2 content (C2) (mass%) relative to 100 mass% of the surface layer of the ceria particle and the MoO3 content (M2) (mass%) relative to 100 mass% of the surface layer of the ceria particle.

[0124] <Result> The values ​​obtained from the above evaluations are shown in Table 1. Note that "ND" is an abbreviation for "not detected," indicating that the substance was not detected.

[0125] [Table 1]

[0126] Scanning electron microscope (SEM) images of the powders of the above-mentioned Examples and Comparative Examples are shown in Figures 1 to 3. Granular or polyhedral particles were observed in each of the Examples and Comparative Examples.

[0127] The results of the XRD analysis are shown in Figure 4. Peaks derived from ceria (CeO2) were observed in the samples of each of the examples and comparative examples.

[0128] From the results of the SEM observation and XRD analysis described above, it was confirmed that the powders obtained in the examples and comparative examples were ceria particles containing ceria.

[0129] Comparing Examples 1 and 2, when sodium molybdate dihydrate was used as a fluxing agent, the crystal growth surface area was larger and the growth rate was faster, so the particle size (D 10、 D50 , and D 90 Each value) and crystallite size ([ 100 ] surface and [ 101 This indicates that the particle size of the produced ceria particles can be easily controlled by calcining a cerium compound in the presence of a molybdenum compound.

[0130] Furthermore, as shown in Table 1, from the results of the MoO3 content (M1) and the MoO3 content (M2), the ceria particles of Examples 1 and 2 contain molybdenum on the surface, and it is expected that various actions due to molybdenum, such as catalytic activity, will be exhibited.

[0131] Furthermore, as shown in Table 1, the surface layer uneven distribution ratio (M2 / M1) of the MoO3 content (M2) to the MoO3 content (M1) shows that the molybdenum oxide content in the surface layer of the ceria particles determined by XPS surface analysis is greater than the molybdenum oxide content determined by XRF analysis in the ceria particles of Examples 1 and 2. This confirms that molybdenum is unevenly distributed in the surface layer of the ceria particles, and it is expected that various functions due to molybdenum will be effectively exerted.

[0132] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims. [Industrial Applicability]

[0133] According to the ceria particles and the manufacturing method thereof of the present embodiment, it is possible to obtain ceria particles having a controlled particle size and particle size distribution.

Claims

1. Ceria particles having a crystallite size of 250 nm or more on the [100] plane and having molybdenum unevenly distributed in the surface layer.

2. The ceria particles according to claim 1 , wherein the crystallite size of the [101] plane of the ceria particles is 300 nm or more.

3. The median diameter D of the ceria particles calculated by a laser diffraction / scattering method 50 The ceria particles according to claim 1 or 2, wherein the average particle diameter is 5.00 μm or more and 1000.00 μm or less.

4. CeO relative to 100 mass% of the ceria particles determined by XRF analysis of the ceria particles 2 Content rate C 1 is 60.00% by mass or more and 99.30% by mass or less, The amount of MoO relative to 100 mass% of the ceria particles determined by XRF analysis of the ceria particles 3 Content rate M 1 The ceria particles according to any one of claims 1 to 3, wherein the ceria content is 0.05 mass% or more and 40.00 mass% or less.

5. The amount of CeO relative to 100 mass% of the surface layer of the ceria particle, which is determined by XPS surface analysis of the ceria particle, 2 Content rate C 2 is 10.00% by mass or more and 90.00% by mass or less, The MoO content relative to 100 mass % of the surface layer of the ceria particle determined by XPS surface analysis of the ceria particle is 3 Content rate M 2 The ceria particles according to any one of claims 1 to 4, wherein the ceria content is 2.00 mass% or more and 70.00 mass% or less.

6. The amount of MoO relative to 100 mass% of the ceria particles determined by XRF analysis of the ceria particles 3 Content rate M 1 The MoO content relative to 100 mass % of the surface layer of the ceria particle, which is determined by XPS surface analysis of the ceria particle, 3 Content rate M 2 Surface uneven distribution ratio M 2 / M 1 The ceria particles according to any one of claims 1 to 5, wherein the Ceria particle diameter is 0.05 or more and 1400.00 or less.

7. A method for producing the ceria particles according to any one of claims 1 to 6, comprising the steps of: A method for producing ceria particles comprising calcining a cerium compound in the presence of a molybdenum compound.

8. The method for producing ceria particles according to claim 7, wherein the molybdenum compound is at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate and sodium molybdate.

9. The method for producing ceria particles according to claim 7 or 8, wherein the firing temperature is 800° C. or more and 1600° C. or less.

Citation Information

Patent Citations

  • Method for producing nano-ceria powder

    JP2002201023A

  • Cerium oxide and method for manufacturing the same

    JP2009067627A

  • Fuel additive containing lattice-operated cerium dioxide nanoparticles

    JP2012512127A

  • Polishing liquid, polishing liquid set, and substrate polishing method

    JP2017139350A

  • Molybdenum-vanadium-niobium-ceria-based catalyst for oxidative dehydrogenation of alkanes and / or alkene oxidation

    WO2018015479A1